In vivo kinematic study of lumbar center of rotation under different loads - Zhenyu Li; Ziwen Liu; Yuming Yang; Zepei Zhang; Lin Meng; Jun Miao (BMC Musculoskeletal Disorders)
Abstract Background Dual fluoroscopic imaging system (DFIS) was employed to identify the Center of Rotation(COR) in the lower lumbar spine and determine its relationship with weight bearing. Methods In this study, twenty participants were recruited. A 3D model of each participant’s lumbar spine was created using CT images, and their relative positions were determined through DFIS. By integrating CT imaging with DFIS, the kinematic data of the participants’ spines during movement were captured. The lower lumbar spine’s COR was calculated using the method of perpendicular bisectors. Results While flexing and extending, the Center of Rotation (COR) initially moved downward with increasing load, followed by upward movement as the load further increased. During flexion and extension, the COR coordinates of L3-4 at 0 kg, 5 kg and 10 kg are(0.3549 ± 0.2176,0.0177 ± 0.1317),(0.0598 ± 0.2095,-0.1806 ± 0.1719),(0.1427 ± 0.1440,-0.0911 ± 0.2722); The center of rotation coordinates of L4-5 at 0 kg, 5 kg and 10 kg are(0.0566 ± 0.2693,-0.0727 ± 0.2132),(0.0964 ± 0.2671,-0.2037 ± 0.2299),(0.1648 ± 0.1520,-0.0049 ± 0.1641). The anterior-posterior position of the COR shifted posteriorly with increasing weight-bearing. During lateral bending, the center of rotation coordinates of L3-4 at 0 kg, 5 kg and 10 kg are(0.0745 ± 0.1229,0.0966 ± 0.3403) (-0.0438 ± 0.1281,0.1161 ± 0.1584), (-0.0464 ± 0.1517,0.1320 ± 0.2730); The center of rotation coordinates of L4-5 at 0 kg, 5 kg and 10 kg are(-0.0314 ± 0.1411,-0.0355 ± 0.2088), (-0.0764 ± 0.3135,0.0105 ± 0.3230),(-0.0376 ± 0.1701,0.0285 ± 0.2395). Throughout the lateral bending exercises, the upper and lower COR positions increased as the load increased, while the left and right COR positions remained unaffected by the load increment. The COR height differed between flexion and lateral bending. We observed variations in the COR position of the lumbar spine during lateral bending and flexion-extension movements. This enhanced our comprehension of coupled motion patterns within the lumbar spine. Conclusions Position of the lumbar spine COR changes with variations in the load. During different movements, the COR location of the lower lumbar spine varied. This finding suggests the presence of distinct motion patterns in the lower lumbar spine. As the load increases, the lumbar COR position changes significantly. Abnormal movement patterns of the lower lumbar spine under different loads may be one of the factors that accelerate lumbar disc degeneration.